2008
DOI: 10.1002/jor.20595
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MHC mismatch and freezing on bone graft incorporation: An experimental study in rats

Abstract: Cortical bone graft failure develops for poorly defined reasons, and the effects of the immune responses on the incorporation of an allograft are less clear. In a rat model of tibial allotransplantation, we have studied biometric and histological changes of the graft and the humoral immune response against it. We have also compared fresh with prefrozen grafts to study putative effects of freezing on the healing of the graft and the immune response against it. Fresh and frozen cortical bone grafts matched or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…We found that long term freezing of the allograft did not induce any detectable antibody response nor impeded healing of the graft. Previously we have shown that the antibody response we have measured reflects immune responses in general, 7 and our present results indicate that deep freezing of bone allograft for 1 year has been sufficient to destroy immunogenicity.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We found that long term freezing of the allograft did not induce any detectable antibody response nor impeded healing of the graft. Previously we have shown that the antibody response we have measured reflects immune responses in general, 7 and our present results indicate that deep freezing of bone allograft for 1 year has been sufficient to destroy immunogenicity.…”
Section: Discussionsupporting
confidence: 73%
“…PVG rats promptly reject organ grafts from PVG.1U rats on the basis of differences in the MHC region, and we and others have shown strong immunological reactions after MHC mismatched transplantation of fresh bone. 6,7 However, allogeneic bone for clinical application is usually stored deep frozen for longer periods of time, and in the present experiments we studied aspects of immunity and outcome of bone bank grafts. We employed rats of a similar body weight that were genetically identical except for the major histocompatibility complex region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Histology at 8 weeks after grafting of a non-vascularised graft showed normal osteocyte density with signs of revascularisation and remodelling; the grafts were well-integrated, with a continuous bridge of hard tissue between the implant and the cortical bone of the host. 34 Direct contact of soft tissues to bone is not a prerequisite for osteogenesis, which may be achieved by soluble factors. [11][12][13][14] It is unclear whether vascularity is essential for osseous integration of reinserted cortical lids.…”
Section: Discussionmentioning
confidence: 99%
“…When allografts were first being used, fresh allografts, rather than fresh frozen were used and incited a marked inflammatory and rejection response which was characterised by a perivascular high density of infiltrating cells and lymphocyte invasion 15. An experimental study in rats suggested that the fresh-frozen technique, which is currently a major allograft processing method as is the freeze-dried process, impeded the antibody response to major histocompatibility complex antigens in bone allografts and improved incorporation compared with fresh allografts 70. A comparative experiment between fresh-frozen and freeze-dried allografts concluded that incorporation and replacement of fresh-frozen bone allografts were delayed compared with the freeze-dried bone allografts 71.…”
Section: Current Evidencementioning
confidence: 99%